Debates on sound in the 1970s and 1980s and the beginning of vocational training for sound editors at VGIK. (4th May 2019) - Rusinova, Elena
ABSTRACT: Part of a special issue devoted to the centenary of the Film Institute VGIK, this article consists of an introduction to and contextualisation of the publication of archival materials that open up important aspects of the relationship between the Soviet state structures and the creative film community at the end of the 1970s and early 1980s. The excerpts from archival texts, published here for the first time, reveal the organisational and technical, as well as the creative and artistic conditions of sound design in Soviet Russian cinema in the specified period, and explain the context in which the idea of the establishment of a sound department at VGIK emerged and how it was implemented.